Origem e evolução dos Helitrons - Pedro Heringer Lisboa Teixeira (2022)
Transposable elements (TEs) are mobile DNA sequences found in a large number of copies in prokaryotic and eukaryotic genomes. In eukaryotes, TEs can be divided into two classes, named class I, which use RNA intermediates to transpose, and class II, which use DNA intermediates. Each one of these classes include different subclasses, which in turn are divided into superfamilies and families. Helitrons represent a subclass of elements within class II that transpose by a mechanism that is unique in eukaryotes, being found in all major taxonomic groups from this domain of life. These transposons impact eukaryotic genomes by occupying considerable DNA fractions of their hosts, also being involved in the mobilization and duplication of adjacent chromosomal fragments. Although the understanding about several aspects related to Helitrons has advanced considerably in the two decades that followed their discovery, their evolutionary origin and details of their transposition mechanism are subjects that remained largely unexplored during the same period. In this work, we investigate the origin of Helitrons using evolutionary analyses of the two major domains present in their transposase. The results from the analyses of each domain reveal distinct, albeit complementary, aspects about the origin of Helitrons. Together, our findings indicate that these elements descend from procaryotic plasmids that, after invading eukaryotic genomes, started using transposition as the replication mechanism in their hosts. This scenario opposes the main hypotheses that have been advanced to explain the origin of Helitrons and the domains of their transposase. Furthermore, based on the evidence provided in this work and other studies, we propose that Helitron transposases execute more complex catalytic functions than it was previously suggested. Finally, our parallel investigation about the evolution of a Helitron family found in arthropods illustrate the marked capacity of these transposons to invade new host genomes through horizontal transfers that can occur between distinct orders or even classes of organisms.